Ontologie-basierte Monosemierung - Kleb, Joachim (KIT Scientific Publishing, 2015)
According to the Semantic Web a formal representation of knowledge is described by an ontology. This formal representation enables a unique identification of elements within an ontology. By the use of natural language for element annotation, ambiguity occurs and a unique element identification based on natural language cannot be guaranteed. This book describes an approach to identify the most relevant element described by a natural language term by reducing the aspect of ambiguity to a minimum.